Authentication and quality control of some polyherbal oils used in Persian Traditional Medicine (PTM) - A. Hamedi; A. Sakhteman; F. Ahmadi; M. Sohrabpour; M.M. Zarshenas (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Traditional polyherbal oils are still in use in Persian Traditional Medicine (PTM). Most of these formulations are prepared via traditional procedures such as maceration of herbs in oils or evaporating aqueous herbal extracts in boiling or heating oils as the vehicle. Thus, their quality control, standardization and authentication are real challenges due to the lack of scientific studies.  The present study provided data and methods to authenticate some of these oils and has compared applicability of different fingerprinting methods for their authenticity. Methods: Thirteen oils were prepared according to the traditional manuscripts. High performance thin layer chromatography (HPTLC), ultraviolet (UV) and infrared (IR) fingerprinting data were analyzed using MATLAB software. For HPTLC fingerprints a special coding system was designed according to the Rf values. The fingerprinting data were subjected to principal components (PCs) analysis. Melting point and thermal behavior of the oils were obtained by differential scanning calorimetry (DSC). Also, the refractive indices, acid and peroxide values were obtained for the oils. Results: The designed coding system for HPTLC was successfully able to produce a discriminative unique fingerprint for each sample. Among UV, IR and HPTLC fingerprinting, the last one seemed more reliable than others to authenticate the oils. The acid values (0.22-3.85), peroxide values (2.31-34.35 meq/kg) and refractive indices (1.4622 - 1.4706) were in acceptable ranges for most of these oils. Conclusion: Despite lack of knowledge about constituents of traditional polyherbal oils, this study was able to provide some data and fingerprinting methods for their authentication.